Performance of a clinical/proteomic panel to predict obstructive peripheral artery disease in patients with and without diabetes mellitus - Nasrien Ibrahim; Renata Mukai; Craig Magaret; Rhonda Rhyne; Grady Barnes; Roland R J van Kimmenade; James L Januzzi; Cian P McCarthy; Shreya Shrestha; Hanna K Gaggin; Joseph M Garasic (Open Heart)
Background Patients with diabetes mellitus (DM) are at substantial risk of developing peripheral artery disease (PAD). We recently developed a clinical/proteomic panel to predict obstructive PAD. In this study, we compare the accuracy of this panel for the diagnosis of PAD in patients with and without DM.Methods and results The HART PAD panel consists of one clinical variable (history of hypertension) and concentrations of six biomarkers (midkine, kidney injury molecule-1, interleukin-23, follicle-stimulating hormone, angiopoietin-1 and eotaxin-1). In a prospective cohort of 354 patients undergoing peripheral and/or coronary angiography, performance of this diagnostic panel to detect ≥50% stenosis in at least one peripheral vessel was assessed in patients with (n=94) and without DM (n=260). The model had an area under the receiver operating characteristic curve (AUC) of 0.85 for obstructive PAD. At optimal cut-off, the model had 84% sensitivity, 75% specificity, positive predictive value (PPV) of 84% and negative predictive value (NPV) of 75% for detection of PAD among patients with DM, similar as in those without DM. In those with DM, partitioning the model into five levels resulted in a PPV of 95% and NPV of 100% in the highest and lowest levels, respectively. Abnormal scores were associated with a shorter time to revascularisation during 4.3 years of follow-up.Conclusion A clinical/biomarker model can predict with high accuracy the presence of PAD among patients with DM.Trial registration number NCT00842868.